An analytical solution and computer simulation for a multi-plate thermoacoustic system. (2nd May 2005) - Mahmud, Shohel; Fraser, Roydon Andrew
In this paper, an analytical model for a multi-plate thermoacoustic system is developed. The governing momentum and energy equations are simplified to quasi-one-dimensional forms using reasonable approximations. The expressions for the fluctuating velocity (u1 ), fluctuating temperature (T1 ), Nusselt number (Nu), fluid friction irreversibility (NsFF ), heat transfer irreversibility (NsHT ), energy flux density (Ė) and transverse velocity (v1 ) are derived using a first order perturbation expansion of the governing momentum and energy equations. Finally, a wave equation is modelled for the present problem by using the continuity, momentum and energy equations.